Anterior Mediastinal Mass in a Young Marijuana Smoker: A Rare Case of Small-Cell Lung Cancer - Jiten P. Kothadia; Saurabh Chhabra; Alan Marcus; Michael May; Biren Saraiya; Salma K. Jabbour (Case Reports in Medicine)
The use of cannabis is embedded within many societies, mostly used by the young and widely perceived to be safe. Increasing concern regarding the potential for cannabis to cause mental health effects has dominated cannabis research, and the potential adverse respiratory effects have received relatively little attention. We report a rare case of 22-year-old man who presented with bilateral neck lymphadenopathy, fatigue, and sore throat without significant medical or family history. The patient had smoked one marijuana joint three times a week for three years but no cigarettes. Chest CT demonstrated a large anterior mediastinal mass compressing the superior vena cava and mediastinal lymphadenopathy. A final diagnosis of small-cell lung cancer was reached. Although rare, a small-cell lung cancer in this patient should alert the physician that cannabis smoking may be a risk factor for lung cancer.